Grenada: recent developments compensatory policies to counteract the negative social impact of adjustment: country paper (ILO. PREALC Port of SpainTT, 1991)
Evaluates the reforms adopted by Grenada in its attempt to create a fiscal regime that is contributory and responsive to economic growth. Sees these reforms as growth oriented with mainly positive implications although there were several political, technical and administrative difficiencies.
DC